Dengue Hemorrhagic Fever (DHF) Surveillance Officer Performances in DHF Control Program in North Semarang District - Hargianti Dini Iswandari; Okti Trihastuti Dyah Retnaningrum (Indonesian Journal of Global Health Research, 2022)
One of the Dengue Control programs is DHF Health Surveillance Officer (GASURKES) according to the Semarang City Regulation Number 5 of 2010, which was then supplemented by the Semarang City Mayor Regulation No. 27 B of 2012 concerning Instructions for Implementing Regional Regulation No. 5 of 2010. However, the incidence of DHF in Semarang City in 2015-2020 has not yet reached the national DHF incidence rate target. Therefore, there is a need for an in-depth study of the performance of Health Surveillance Officers and a description of the factors that affect performance as a description of the condition of health workers. The purpose of this research is to describe and analyze the performance of GASURKES in a dengue control program. This research is qualitative research conducted in North Semarang District. The main informant in this study was the DHF surveillance officer, while the triangulation informant was the coordinator of the health surveillance officer. The sample was determined through the purposive sampling technique. Data collection was carried out by in-depth interview method. Data were analyzed using qualitative data analysis. The results of the study indicate that the knowledge of health surveillance officers (GASURKES) in the North Semarang District is quite good. The description of GASURKES' workload is still high and tends to be multi-job. The motivation factor for GASURKES is still lacking because it is related to the lack of rewards received compared to the high workload. Health Resources for the implementation of dengue control efforts are sufficient. However, the performance of health surveillance officers (GASURKES) in the North Semarang District has reached the work target.